Formulation and in vitro characterization of trimetazidine oral in situ gel - Gonzales, Jade C.; Kimayong, Hazelyne D.
Over the past years, gastroretentive drug delivery systems (GRDDS) have been gaining attention for its improved therapeutic advantages, such as ease of administration, patient compliance and flexibility in formulation. Part of the GRDDS are the in situ gelling systems. This study aimed to formulate and evaluate the floating oral in situ gel of the anti- angina drug, Trimetazidine. Sodium alginate was used as the main gelling polymer, along with the other natural polymers, pectin and xanthan gum. Sodium bicarbonate was used as floating agent and release rate controller. The resulting formulation undergoes gelation upon exposure to acidic media. A two-factor, three-level factorial design was performed and the effects of varying the concentration of sodium alginate and sodium bicarbonate on the pH, viscosity, floating lag time, drug content and drug release at Ihr were investigated. Results indicate that there was no sufficient evidence to show that the sodium alginate concentration, sodium bicarbonate concentration, and the interaction between sodium alginate and sodium bicarbonate significantly affect the pii, viscosity, floating lag time, and drug release at Ihr. Drug content, on the other hand, was significantly affected by the sodium alginate concentration and the interaction between sodium alginate and sodium bicarbonate. The drug release mechanism of most of the formulations followed Korsmeyer- Peppas model specifically a Quasi-fickian diffusion mechanism. Upon comparison with the commercially available tablet, a relatively similar release trend was observed but the in situ gel formulation had a higher release on the first hours due to the burst effect of the polymers.